Determinants of Client Acceptance Decisions and the Impact on the Reputation of Public Accounting Firms in Indonesia - Afly Yessie; Ilya Avianti; Poppy Sofia (Australasian Accounting, Business and Finance Journal, 2023)
This study empirically aims to prove the effect of client acceptance decisions on improving the reputation of public accounting firms. This research was conducted with a quantitative approach sourced from primary data. The data was obtained from 210 respondents who are audit partners of public accounting firms (KAPs) and have a practice license from the Ministry of Finance of the Republic of Indonesia. The analytical tool used in this research is Structural Equation Modeling (SEM) analysis. The results showed that: the client's business risk, audit risk, and public accounting firm risk have a negative effect on client acceptance decisions, and audit fees have a positive effect on client acceptance decisions; Furthermore, the decision to accept clients affects the reputation of the public accounting firm. Conversely, public accounting firm risk does not affect the reputation of the public accounting firm. Public accountants in audit practice are expected to have the expertise to decide whether to accept audit clients. The reputation of public accounting firms may be affected by this decision.
Keywords: Client acceptance decision; Indonesia; the reputation of the public accounting firm; client& #x27; s business risk; audit risk; KAP risk; Audit fee